Tuberculous meningoencephalitis in children (1977)
A study is made of 41 children with tuberculous meningoencephalitis in the Hospital Infantil Lorencita Villegas de Santos de Bogota, over a period of 7 years. The disease occurs principally in ill-nourished children under 4 years of age and is favoured by the crowded conditions of the family. An analysis is made of the clinical conditions of the affection and its sequels. Its diagnosis is difficult to make accurately by the diagnostic methods available at the present time, but in this great help is given by X-rays of the thorax and the clinical signs of the meningeal syndrome, plus signs of focalisation. The majority of cases are admitted to hospital in an advanced stage.